Policy Effectiveness of Social Assistance for Religious Minority Group in Sidoarjo Regency - Baharuddin Riqiey; Wiwik Afifah (Proceeding International Conference on Religion, Science and Education, 2023)
The social assistance policy is a concrete form of the government’s responsibility towards the condition of its people who are underprivileged and neglected at the city and regional levels, this social assistance policy is intended for anyone who experiences a situation that is not solid as a result of social, economic, political crises, disasters, or natural phenomena in order to be able to meet the minimum necessities of life, so that is not a reason not to provide social assistance to certain groups. The government is seeking social assistance in various forms such as BLT, PKH, BPNT, and others. The purpose of this study was to determine the effectiveness of social assistance policies for religious minority groups in Jemundo Village, Sidoarjo Regency, as well as any problems experienced by religious minority groups related to social assistance. The method used in this research is empirical juridical research with a sociological approach. The findings in this study are the effectiveness of social assistance for religious minority groups in Sidoarjo which is quite effective, but this is only effective in the short term where they directly use it to meet basic food costs, children’s school fees that are not covered by PKH, and are used for family food. Meanwhile regarding the problem, the religious minority group in Jemundo village, is almost the same as the problem of recipients who are not a religious minority group. However, religious minority groups still receive the stigma that they are taking the “allocation” of the poor community of Jemundo village.